PERLINDUNGAN HUKUM TERHADAP MEREK BATIK DI KOTA PEKALONGAN DALAM MENYONGSONG ASEAN ECONOMIC COMMUNITY 2015 - Anis Mashdurohatun; Adriyanto Adriyanto (UNISSULA, 2014)
In the facing of the ASEAN Economic Community 2015, the Legal Protection of batik brand in Pekalongan plays a very important and requires a more adequate regulatory system. Free trade globalization can only be maintained by maintaining a healthy climate for business competition. The demand for legal protection of batik brand is growing rapidly as the number of people who plagiarized brand of batik. One brand that needs to be protected is the batik brand of Pekalongan as the largest industrial centers of batik in Indonesia. The methods of This research uses empirical juridical approach to the specification of descriptive analytical study which the author tries to explain the preparation of batik pekalongan society Towards the ASEAN Economic Community in 2015. So far if there is a dispute in the brand of batik fairly resolved peacefully and families, but in the case of infringement of trademark of batik, then the holder of legitimate trademark rights can be conduct civil or criminal action lawsuit to court, or can be resolve by arbitration as an alternative, such as regulated in Act No. 30 of 1999 on Arbitration and alternative dispute resolution.